Fabrication of cellulose nanofiber‐based ultrafiltration membranes by spray coating approach. Issue 11 (4th November 2016) - Wang, Zhe; Ma, Hongyang; Chu, Benjamin; Hsiao, Benjamin S.
ABSTRACT: Ultrafiltration membranes containing a cellulose nanofiber barrier layer were fabricated by the spray coating method, where the thickness and uniformity of the barrier layer were systematically investigated as a function of air pressure, flow rate and concentration of the cellulose nanofiber suspension. In specific, the surface morphology of the barrier layer was studied by scanning electron microscopy and its uniformity was examined by the fluorescence dye imaging method. The ultrafiltration performance of the membranes fabricated by the spray coating method was also compared with that of the membranes made by the knife coating approach using dextran molecules as probe, where the former consistently exhibited significantly higher permeation flux while remaining the same rejection ratio. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 44583. Abstract :